EFEKTIVITAS UNIT PENGUMPUL ZAKAT (UPZ) DALAM MENINGKATKAN JUMLAH ZAKAT, INFAQ, DAN SEDEKAH TERHADAP PENINGKATAN KESEJAHTERAAN EKONOMI MUSTAHIK DESA MARGAHARJA - Eris Munandar (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2022)
The Zakat Collecting Unit (UPZ) is in charge of collecting zakat and distributing it to mustahik as determined. This study aims to describe the effectiveness of the Zakat Collecting Unit (UPZ) in increasing the amount of zakat, infaq and alms funds towards increasing the Mustahik Economic Welfare of Margaharja Village. This study uses a qualitative method. Techniques for collecting data using surveys and interviews. The technique for taking samples is random sampling, which gives equal rights to each subject to have the opportunity to be selected as a sample, the sample is taken at random and according to the researcher's considerations. The results showed that the Zakat Collecting Unit (UPZ) Margaharja was successful in increasing the amount of zakat, infaq and alms funds by collecting zakat funds using the pick-up method. in 2019. Through a work program compiled by the Zakat Collecting Unit (UPZ) Margaharja seeks to change the status of mustahik to muzakki or prosper.